2013
DOI: 10.17659/01.2013.0030
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in Children Requiring Hospitalization

Abstract: Abstract:This prospective study evaluated the frequency, etiological causes of children with hyponatremia (serum sodium< 135 mEq/L) in 500 children aged between 1 month and 14 years of age admitted at tertiary care hospital in Rajasthan, India. Hyponatremia was found in 37% (185/500). Meningitis/encephalitis accounted for 20.5% followed by pneumonia and acute diarrhea each accounting for 12.43% of cases. Other causes were septicemia (7.6%), seizure (7.6%), cardiac diseases (3.2%), renal diseases (5.3%), liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The observations in present study were consistent with the prospective study by Subba Rao et al, [7] wherein CNS cause accounted for 41.6% of the hyponatraemic admissions. Sitaraman S et al [28] found meningitis/encephalitis as single most important cause of hyponatraemia accounting for 20.54% of cases. Different causes reported by Singhi et al [5] in their study were pneumonia (20%), acute gastroenteritis (20%), meningoencephalitis (12%), sepsis (8%), renal, CVS and liver causes (6.7%).…”
Section: Spectrum Of Illnessesmentioning
confidence: 99%
“…The observations in present study were consistent with the prospective study by Subba Rao et al, [7] wherein CNS cause accounted for 41.6% of the hyponatraemic admissions. Sitaraman S et al [28] found meningitis/encephalitis as single most important cause of hyponatraemia accounting for 20.54% of cases. Different causes reported by Singhi et al [5] in their study were pneumonia (20%), acute gastroenteritis (20%), meningoencephalitis (12%), sepsis (8%), renal, CVS and liver causes (6.7%).…”
Section: Spectrum Of Illnessesmentioning
confidence: 99%